KORELASI ANTARA LAYANAN KONSELING INDIVIDUDENGAN PEMILIHAN STUDI LANJUTAN SISWA DI SMP NEGERI 2 BARRU - Rukaya, Rukaya (Journal of Innovation Research and Knowledge, 2025)
The main problem raised in this thesis is how the correlation between individual counseling services and the selection of further studies of SMP Negeri 2 Barru students. The research is quantitative research with the type of research using correlational research, with a population of 466 people and a sample of 47 people. The data collection used is observation, questionnaire, and documentation techniques, while the data analysis technique uses correlation product moment. The results of this study found that the category of correlation or contribution between variables was o.42 which means high, while the results of hypothesis testing showed a significant correlation between the two variables. Based on the results of the study, it can be seen that there is a significant correlation between guidance and counseling on the moral development of students at SMP Negeri 2 Barru